Modelagem in silico de PK/PD da doramectina a 3,5% em bovinos para o tratamento de Rhipicephalus microplus em bovinos - Nogueira, Lucas Milagres (2022)
The use of antiparasitic agents over the years has contributed significantly to the increase productivity in cattle farming. Specifically, the macrocyclic lactones, especially doramectin, have great importance in this context because they have low toxicity, broad spectrum of action, and biological activity in small concentrations. However, new paradigms for the use of this class of drugs have been raised to promote their use in a more rational way, in order to mitigate the selection of resistant parasites and minimize eventual environmental impacts. Concerns are due because a large proportion of the drugs are not completely metabolized and elimination may occur as unchanged drug and/or bioactive metabolites after treatment of the animals, consequently, the release of the drug into the environment may have a potential impact on the ecosystem balance of living organisms in a negative way and the selection of resistant individuals. In search of solutions, pharmacokinetic/pharmacodynamic (PK/PD) modeling is the initial step in the approach for the optimization of dosage regimens, seeking to obtain the maximum performance of the drugs, thus, besides promoting greater efficacy, will be able to decrease the number of residues sent to the environment and the selection of resistant organisms. The PK/PD model was prepared using the parameters obtained from the PK model and the average efficacy data of doramectin 3.5% against Rhipicephalus microplus in experimentally infected cattle from the work done by Righi (2013) using Lixoft® Monolix 2020R1 software. From the PK/PD model, the efficacies against ticks were simulated after administration of 350, 700 and 1050 ug/Kg doramectin 3.5 % (subcutaneously) over 90 days. The structural PK model of doramectin, administered to cattle by the subcutaneous route established was oral/extravascular route, with transit compartments, first-order absorption, two-compartment distribution, and linear elimination kinetics. The model predicted plasma doramectin values in cattle in an appropriate manner, showing an adequate correlation between observed and predicted values, with a homogeneous dispersion along the predicted value line within 90%. The lines of the observed values of the 5th percentile and the median were within their respective predicted 95% confidence intervals (shaded area). In turn, it was observed that the model underestimates the maximum concentration (Cmax) of the observed 95th percentile values, but this maximum concentration would not impact the efficacy of the medication. The pharmacokinetic model proposed by this work met the requirements and proved to be a promising tool, therefore the model was able to adequately predict the doses of doramectin 3.5% in cattles. This way, studies like this one can bring benefits for dose adjustments and optimizations. In addition, we can consider the development of non-animal methods as legitimately ethical, reducing costs and respecting animal welfare.